Preliminary phytochemical screening test of Garcinia griffithii plant - Kamal, Tara; Zuberdi, Ahmad Muzammil; Abdullateef, Raji Akintunde; Rahma, Muayad Salm; Omar, Muhammad Nor (Academic Information Press, 2012)
Nowadays, researchers are focusing their attention towards folk medicine for developing better drugs against microbial infections. The present study aimed to evaluate the phytochemical constituents from Garcinia griffithii plant. The plant materials were extracted using solvents with different polarities (methanol, ethyl acetate and hexane). The solvent extracts were screened and the results of screening test for phytochemicals showed that, the presence of various metabolites in different solvents. only the phenolic groups were presented in hexane and ethyl acetate extracts, whereas, The methanol extract contains terpenoids, alkaloids, flavonoids, saponins and glycosides, and those chemical compounds possess antibacterial activities against pathogenic microorganisms.